2022
DOI: 10.47750/pnr.2022.13.s08.237
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Counseling and Storytelling Method on the Anxiety Levels of Primary School Children to Receive Covid-19 Vaccine

Abstract: Background: The World Health Organization, WHO explains that sadness and anxiety are the most common mental health problems. Anxiety for children occurs due to the COVID-19 vaccination program by the government may cause uncooperative attitudes. Thus, this situation may lower the children's effectiveness to join learning activities. This research analyzed the influence of counseling with the storytelling method on the anxiety of school learners to receive COVID-19 vaccination in Primary School 03 Bulungcangkri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
0
0
Order By: Relevance
“…These videos effectively reduced vaccine-related anxiety by offering non-pharmacological counseling. As a result, anxiety levels decreased, helping children overcome their fears of getting vaccinated [9]. Likewise, another study demonstrated that storytelling encouraged children to adopt positive COVID-19 preventive behaviors.…”
Section: Discussionmentioning
confidence: 97%
“…These videos effectively reduced vaccine-related anxiety by offering non-pharmacological counseling. As a result, anxiety levels decreased, helping children overcome their fears of getting vaccinated [9]. Likewise, another study demonstrated that storytelling encouraged children to adopt positive COVID-19 preventive behaviors.…”
Section: Discussionmentioning
confidence: 97%